The best of the original An evening at the Improv [videorecording (DVD)] - Kantor, Ron; Seinfeld, Jerry; Carter, Judy, 1950-; Podell, Rick, 1946-; LaMarche, Maurice, 1958-; Keaton, Michael, 1951-; Weiner, Marc, 1955-; Mandel, Howie; Reiser, Paul; Carrey, Jim, 1962-; Townsend, Robert, 1957-; Boosler, Elayne, 1952-; et al. (Somerville House, 2013)
Chosen from the first 52 original hours of the television series, this collection features twelve hours of stand-up comics performing their routines before live audiences at the Improv Club in Los Angeles, California. Also includes introductions and short bits by guest hosts as well as several musical performances.